Program Kuliah Kerja Nyata Tematik (KKNT) : Pentingnya Memahami Tentang Penyakit ISPA, Hipertensi Dan Diet Hipertensi - Ademin, Ravian; Sari, Yulita Mutiara; Asriki, Jespopon; Novsawindi, Efrizal; Atini, Masreka; Ariska, Inten; Aprianti, Delta; Suyanto, Jipri; Rohani, Tuti; Azissah, danur (Universitas Dehasen Bengkulu, 2025)
Thematic Real Work Lecture Program (KKNT) activities. Real Work Lectures (KKN) is a community service program carried out by students as part of the lecture curriculum. This research aims to analyze the experience and impact of KKN on the community and student participants. The research method uses a qualitative approach with data collection techniques through interviews, observation and document analysis. The research results show that KKN has a positive impact on society, such as increasing awareness of health, education and the economy. Meanwhile, students participating in KKN experienced increased communication, leadership and empathy skills. The KKN program also contributes to the development of a more independent and sustainable community. Pagar Gading Village has an area of ​​120 Ha located in Pino Raya District, South Bengkulu Regency, with 339 heads of families and a population of 1,546 people. The high incidence of Upper Respiratory Tract Infections (ARI) & Hypertension and the lack of public knowledge about these diseases encourage Dehasen University students to provide health education to the community to provide a better understanding. Data collection uses primary data obtained from the results of questionnaires distributed to the community and secondary data obtained from the Pagar Gading Community Health Center. The method for evaluating the implementation of the Real Work Lecture (KKN) activity program is reviewed from the sustainability of the program's effectiveness, the sustainability of the program on the targets of each work program.